Production of an Enzymatic Extract From Aspergillus oryzae DIA-MF to Improve the Fructooligosaccharides Profile of Aguamiel - Picazo, Brian; Flores-Gallegos, Adriana C.; Ilina, Anna; Rodríguez-Jasso, Rosa María; Aguilar, Cristóbal N. (Frontiers in Nutrition, 2019)
Aguamiel is a natural sap produced by some species of agave plants, such as A. salmiana, A. atrovirens or A. angustifolia. It is a product with a high concentration of fructose, glucose or sucrose, although its composition may vary depending on the season in which it is produced, and may also contain agave fructans (or agavins) or fructooligosaccharides (FOS). It has been reported that FOS can be produced by enzymes that act on sucrose or inulin, transfructosylating or hydrolyzing these materials, respectively. Due to the sugar content in aguamiel, the application of an enzymatic complex produced by A. oryzae DIA MF was carried out. This complex was characterized by 1-D electrophoresis SDS-PAGE, and its transfructosylation and hydrolysis activities were determined by HPLC. In order to determine the conditions at which the concentration of FOS in this beverage was increased, kinetics were carried out at different temperatures (30, 50 and 70 ° C) and times (0, 1, 2, 3, 4, 5, 10 and 15 h). Finally, the antioxidant and prebiotic activity were evaluated. FOS concentration in aguamiel was increased from 1.61 ±0.08 to 31.01 ±3.42 g/ L after 10 h reaction at 30 °C applying 10% enzymatic fraction-substrate (v/v). Antioxidant activity was highly increased (34.81 to 116.46 mg/ eq Trolox in DPPH assay and 42.65 to 298.86 mg/ eq Trolox in FRAP assay) and growth of probiotic bacteria was higher in aguamiel after the enzymatic treatment. In conclusion, after the application of the enzymatic treatment, aguamiel was enriched with FOS which improved antioxidant and prebiotic properties, so it can be used as a functional food.